RILEM 252-CMB Symposium Chemo-Mechanical Characterization of Bituminous Materials - Poulikakos, Lily D.; Cannone Falchetto, Augusto; Wistuba, Michael P.; Hofko, Bernhard; Porot, Laurent; Di Benedetto, Hervé; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume contains the Proceedings of the RILEM TC 252-CMB International Symposium on the Chemo-Mechanical Characterization of Bituminous Materials. The Symposium was attended by researchers and practitioners from different fields presenting the latest findings in the chemical, mechanical, and microstructural characterization of bituminous materials. The book offers new and cutting edge papers on innovative techniques for the characterization of bituminous materials, gaining new insights into current issues such as effects of aging, moisture, and temperature. .
Part I Chemo-Mechanical Characterization of Bituminous Materials: Bitumen Aging Mechanisms and Characterization -- A Mechanism Based Reaction-Diffusion Model for Spurt Oxidation of Bitumen, by Uwe Mühlich -- Aging Characterization of Biobinder Produced from Renewable Sources, by Ingrid Gabrielle do Nascimento Camargo, Liedi Légi Bariani Bernucci, Kamilla L. Vasconcelos -- Chemomap Imaging Microscopy use to in Situ Assess Oxidative Ageing in Compacted Asphalt Mixtures, by S. Vassaux, V. Gaudefroy, L. Boulangé, A. Pévère, V. Mouillet -- Comparison of Short Term Laboratory Ageing on Virgin and Recovered Binder from HMA/WMA Mixtures, by Gilda Ferrotti, Hassan Baaj, Jeroen Besamusca, Maurizio Bocci, Augusto Cannone-Falchetto, James Grenfell, Bernhard Hofko, Laurent Porot, Lily Poulikakos, Zhanping You -- Effect of Artificial Ageing on Two Different Bitumen of Different Origin but Same Performance Grade, by Alexandre Rogeaux, Alan Carter, Daniel Perraton, Abdeldjalil Daoudi -- Evaluation of Viscoelastic Properties and Cracking Behaviour of Asphalt Mixtures with Laboratory Aging, by Runhua Zhang, Jo Sias Daniel, Eshan V. Dave -- Microstructural Investigation of Reclaimed Asphalt Binder with Bio-Based Rejuvenators, by Maria Chiara Cavalli, Martins Zaumanis, Lily Poulikakos -- Recommendations of RILEM TC 252-CMB on the Effect of Short Term Aging Temperature on Long Term Properties of Asphalt Binder, by Lily D. Poulikakos, Bernhard Hofko, Augusto Cannone Falchetto, Laurent Porot, Gilda Ferrotti, Peter Mikhailenko -- Rheology and Bituminous binder, a Review of Different Analyses, by Laurent Porot -- Short Term Aging - Influence of Mixing Time at Laboratory Specimen Production, by Daniel Steiner, Daniel Maschauer, and Bernhard Hofko -- Viennese Aging Procedure - Behavior of Various Bitumen Provenances, by Daniel Maschauer, Daniel Steiner, Johannes Mirwald, Bernhard Hofko, Hinrich Grothe -- Part II Chemo-Mechanical Characterization of Bituminous Materials: Chemo-Mechanical Coupling -- AgeingEffect on Chemo-Mechanics of Bitumen, by Ruxin Jing, Aikaterini Varveri, Xueyan Liu, Athanasios Scarpas, Sandra Erkens -- Chemo-Mechanical Characterization of Bitumen Binders with the Same Continuous PG-Grade, by Jean-Pascal Planche, Michael D. Elwardany, Jeramie Adams -- Field Aging Evaluation of Asphalt Binders by Chemical and Rheological Characterization, by Marcia Midori Takahashi, Kamilla L. Vasconcelos, Margareth Carvalho Coutinho Cravo, Liedi Légi Bariani Bernucci -- Modifying Surface Properties of Model and Pavement Aggregates with Silanes, by Gabriel Orozco, Cédric Sauzéat, Jules Galipaud, Hervé Di Benedetto -- Part III Chemo-Mechanical Characterization of Bituminous Materials: Low, Intermediate and High Temperature Behavior -- Effect of Morphology on High-Temperature Rheological Properties of Polymer-Modified Bitumen, by Jiqing Zhu, Xiaohu Lu -- Experimental Investigation of Rutting in the Different Phases of Asphalt Mixtures, by Chiara Riccardi, Augusto Cannone Falchetto, MichaelP. Wistuba -- Investigation on the Effect of Physical Hardening and Aging Condition on Low-Temperature Properties of Asphalt Binder based on BBR, by Di Wang, Augusto Cannone Falchetto, Chiara Riccardi, Michael P. Wistuba -- Laboratory and Field Experience with PMMA/ATH Composite in Asphalt Mixtures, by Marjan Tušar, Mojca Ravnikar Turk -- On the Use of a Novel Binder-Fast-Characterization-Test, by Johannes Schrader, Michael P. Wistuba -- Use of Microencapsulated Phase Change Materials in Bitumen to Mitigate the Thermal Distresses in Asphalt Pavements, by Muhammad Rafiq Kakar, Zakariaa Refaa, Jörg Worlitschek, Anastasia Stamatiou, Manfred N. Partl, Moises Bueno -- Part IV Chemo-Mechanical Characterization of Bituminous Materials: Microstructure and Micro-Mechanics -- Analysis of Bitumen and PmB Using Fluorescence Spectroscopy and Microscopy, by Johannes Mirwald, Hinrich Grothe, Bernhard Hofko, Daniel Maschauer, Daniel Steiner -- Chemical Composition and Microstructure of Bitumen - a Matter ofTerminology?, by Bernhard Hofko, Daniel Maschauer, Daniel Steiner, Hinrich Grothe, Johannes Mirwald -- ESEM Microstructural and Physical Properties of Virgin and Laboratory Aged Bitumen, by Peter Mikhailenko, Hassan Baaj, Lily Poulikakos, Augusto Cannone Falchetto, Jeroen Besamusca, Bernhard Hofko -- Investigation of the Asphalt Binder Sample Preparation Methods based on AFM, by Zhijun Wang, Rong Chang, Zhenyu Zhou, Yongchun Qin, Gaochao Wang -- Precision of Iatroscan Method for Assessment of SARA Compounds in Bitumen, by Diana Simnofske, Konrad Mollenhauer -- Visualization and Chemical Analysis of Bitumen Microstructures, by Xiaohu Lu, Peter Sjövall, Hilde Soenen, Johan Blom, Martin Andersson -- Part V Chemo-Mechanical Characterization of Bituminous Materials: Recycling and Rejuvenation -- A new Green Rejuvenator: Evaluation of Structural Changes of Aged and Recycled Bitumens by means of Rheology and NMR, by Cesare Oliviero Rossi, Paolino Caputo, Valeria Loise, Saltanat Ashimova, Bagdat Teltayev, Cesare Sangiorgi -- A Rheological Study on Rejuvenated Binder Containing very high Content of Aged Bitumen, by Marco Pasetto, Andrea Baliello, Giovanni Giacomello, Emiliano Pasquini -- An Examination of Property Changes of Repeatedly Recycled Asphalt Bitumen using Rejuvenator with High Aromatic Content, by Atsushi Kawakami, Yoko Kawashima, Hiroyuki Nitta, Masayuki Yabu -- Effects of Rejuvenator on Reclaimed Asphalt Binder: An Exploratory Study of the RILEM TC 264-RAP Task Group 3, by Augusto Cannone Falchetto, Laurent Porot, Chiara Riccardi, Martin Hugener, Gabriele Tebaldi, Eshan Dave -- New Binders using Natural Bitumen Selenizza, by Edith Tartari -- Rejuvenated Binders, Reclaimed Binders and Paving Bitumens, are they any Different?, by Tomas Koudelka, Pavel Coufalik, Michal Varaus, and Iva Coufalikova -- Study on the Mechanical Properties of Waste Cooking Oil Modified Asphalt Binder, by Xin Qu, Dawei Wang, Quan Liu, Markus Oeser, Chao Wang -- The Effect of the Nature of Rejuvenators on the Rheological Properties of Aged Asphalt Binders, by Raúl Tauste, Fernando Moreno-Navarro, Miguel Sol-Sánchez, Mª Carmen Rubio-Gámez -- Part VI Chemo-Mechanical Characterization of Bituminous Materials: Multiphase Analysis of Binders -- Effect of Recycled Materials on Intermediate Temperature Cracking Performance of Asphalt Mixtures, by Wei Cao, Louay Mohammad, Peyman Barghabany -- Investigation of the Calculation Modeling of Asphalt Binder Surface Energy based on the Atomic Force Microscope (AFM), by Rong Chang, Erhu Yan, Jian Xu, GaoChao Wang -- Qualitative Detection of the Presence of Gilsonite in the Bituminous Blends based on thin Layer Chromatography, by Michalina Makowska, Terhi Pellinen -- Resistance to Moisture-Induced Damage of Asphalt Mixtures and Aggregate-Binder Interfaces, by Jorge Lucas Júnior, Lucas Babadopulos, Jorge Soares -- Study on Effects of Aging on SBS Modified Asphalt Based on GPC and Rheological Methods, by Daisong Luo, Meng Guo, Yiqiu Tan, Yafei Li -- Part VII Chemo-Mechanical Characterization of Bituminous Materials: Other Approaches -- How to Evaluate with Relevance the Compactability of Warm Mixes Using the Gyratory Compactor (GC), by Abdeldjalil Daoudi, Anne Dony, Layella Ziyani, Nicolas Picard, Julien Buisson -- Hybrid Approach to Characterize Reflective Cracking in Airport Pavements, by Tirupan Mandal, Mesbah Ahmed, and Hao Yin, Richard Ji -- Kinetic Analysis of the Thermal Behavior of the Sap of the Petroleum Plant for Producing Bio-Binders, by Gondim Lilian Medeiros, Soares Sandra de Aguiar, Barroso Suelly Helena de Araújo -- Machine Learning Technique for Interpretation of Infrared Spectra Measured on Polymer Modified Binders, by Adam Zofka, Krzysztof Błażejowski -- Meso- to Macroscale Homogenisation of Hot Mix Asphalt Considering Viscoelasticity and the Critical Role of Mortar, by Johannes Neumann -- Novel Application of the Falling Weight Deflectometer Test: Detection of Surface and Subsurface Distresses, by A. Chatterjee, Y. Tsai -- Peat as an Example of a Natural Fiber in Bitumen, by Hilde Soenen, Patricia Kara De Maeijer, Johan Blom, Wim Van den Bergh -- Promotion of Bitumen-Impregnated Cellulose Fibres from Lightweight Roofing Tiles in Stone Mastic Asphalt, by Clara Tamburini, Layella Ziyani, Anne Dony, Christophe Rohart, Emanuele Toraldo.
Keywords: Building materials; Materials -- Analysis; Mechanics, Applied; Building Materials; Characterization and Analytical Technique; Engineering Mechanics